Analisis Tindak Tutur Direktif dalam Review Produk Online oleh Influencer Fadil Jaidi - Abharina Azaria Setya Ghassani; Aufa Aisyah Zerlina; Hana Khairunnisa; Novrita Andriana Fitri; Asep Purwo Yudi Utomo; Dwi Setiyawan; Ramadhan Kusuma Yuda (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This research aims to analyze the behavior and function of speech acts used by Fadil Jaidi in reviewing products online, which encourages the interlocutor to take action. This research is based on persuasive language, which has a big role in influencing consumers. The methods used in this study are methodological approach and theoretical approach. The data sources used in this study are fragments of speech discourse included in directive speech acts in several videos uploaded by Fadil Jaidi on digital platforms. The results show that there are nine forms of directive speech acts in several online product review videos by influencer Fadil Jaidi, namely (1) suggestive speech, (2) ordering speech, (3) commanding speech, (4) forcing speech, (5) convincing speech, (6) inviting speech, (7) urging speech, (8) questioning speech, (9) requesting speech. With this research, readers are expected to be able to understand the forms of directive speech acts as well as the intentions of the speech performed by Fadil Jaidi through online product review videos.